Antecedents and Consequences of Eudaimonic Tourism Happiness and Attitude Toward Behavior of Stone Garden Tourists West Bandung Regency - Alda Tiara Putri; Yadi Ernawadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of educational, escapist, and aesthetic on revisit intention through eudaimonic tourism happiness and attitude toward behavior of Stone Garden tourists. This study used a quantitative approach with a survey method on 118 Stone Garden tourists. Data were analyzed using structural equation modeling (SEM) with SmartPLS version 3.0. The findings indicate that educational, escapist, and aesthetic have a positive effect on eudaimonic tourism happiness. Eudaimonic tourism happiness influences revisit intention both directly and through attitude toward behavior. In addition, eudaimonic tourism happiness acts as a mediator between escapist and aesthetic on revisit intention. The novelty of this research is the addition of new hypotheses, namely educational and escapist, and attitude toward behavior as additional mediating variables. These findings are expected to contribute to future research and parties involved in the tourism industry to design relevant strategies to improve the quality of these attributes.